Measurement of the spin-density matrix elements in exclusive electroproduction of ρ0 mesons at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Abbiendi, G; et al. (2000)
Exclusive electroproduction of ρ0 mesons has been measured using the ZEUS detector at HERA in two Q2 ranges, 0.25 < Q2 < 0.85 GeV2 and 3 < Q2 < 30 GeV2. The low-Q2 data span the range 20 < W < 90 GeV; the high-Q2 data cover the 40 < W < 120 GeV interval. Both samples extend up to four-momentum transfers of |t| = 0.6 GeV2. The distribution in the azimuthal angle between the positron scattering plane and the ρ0 production plane shows a small but significant violation of s-channel helicity conservation, corresponding to the production of longitudinally polarised (i.e. helicity zero) ρ0 mesons from transverse photons. Measurements of the 15 combinations of spin-density matrix elements which completely define the angular distributions are presented and discussed.